Online shopping web service using rest techniques - Muhammad Umair, 1991- author 632074; Imran Ghani, 1975- supervisor 384609; Fakulti Komputeran 538688 (2015)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2015